Assessing Atmospheric Pollution and Its Impacts on the Human Health - Barbulescu, Alina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contains articles published in the Special Issue entitled "Assessing Atmospheric Pollution and Its Impacts on the Human Health" in the journal Atmosphere. The research focuses on the evaluation of atmospheric pollution by statistical methods on the one hand, and on the other hand, on the evaluation of the relationship between the level of pollution and the extent of its effect on the population's health, especially on pulmonary diseases.